CAREER ASPIRATIONS OF JUNIOR DOCTORS IN PAKISTAN: EXPLORING REASONS BEHIND THE BRAIN DRAIN - Balouch, Malab Sana; Balouch, Mohammad Moaz; Balouch, Mechale Sana; Qayyum, Waqar; Zeb, Zainab (Journal of Ayub Medical College Abbottabad, 2022)
Background: Mass medical migration from Pakistan to more developed counties pose a threat to the professional resources of Pakistan. The aim of our study is to assess magnitude of the brain drain and to assess reasons behind it. Methods: A Cross-sectional study, using convenience non-probability sampling, with sample of 201 Ayub Medical College graduates. A simple questionnaire was designed on Google Forms, comprising of three sections including bio data, intentions to emigrate and the last part evaluating work environment, training and personal factors associated with the desire to train abroad. Data was analysed using SPSS version 20.0, descriptive statistics were calculated and Chi square test was used to determine association between various groups of push and pull factors and the intention to train abroad. A significance level (p-value) of less than 0.05 was used. Results: Over half (63.68%) of our participants wanted to emigrate, and out of the remaining 71.6% would consider it in the future if given the opportunity. Overall, more males wanted to train overseas as compared to females, and the United Kingdom was the most popular destination. The leading factor push factors behind wanting to move abroad were quality of training and a poor work environment. While family commitments and costly examinations were the main reasons to stay in Pakistan. Conclusion: A significant number of young doctors are planning on pursue training/careers abroad. If this large-scale brain drain is not addressed on time, it can have various implications in the future. Hence the Government and Medical authorities must take action in order to prevent further loss.